Penggunaan Robot Mikroskopis untuk Menghantarkan Obat pada Sel Kanker secara Presisi - Nur Aini; Endro Pramono (CV. Aksara Global Akademia, 2024)
Cancer therapy has long faced the challenge of balancing treatment effectiveness with minimizing damage to healthy tissues. Conventional therapies such as chemotherapy and radiotherapy, although widely used, often lead to significant side effects due to their non-specific nature. This study aims to analyze the effectiveness of microscopic robots in delivering drugs precisely to cancer cells, thereby reducing collateral damage. The research employed simulations and in vitro preclinical tests using cancer cell cultures to evaluate both targeting accuracy and safety. Findings indicate that microscopic robots achieved 93% effectiveness in targeting cancer cells while limiting damage to healthy cells to only 10%. Compared to chemotherapy, radiotherapy, chemoradiotherapy, and nanoparticle-based drug delivery systems, microscopic robots demonstrated superior precision and efficiency. These results suggest that microscopic robots hold great potential as a breakthrough technology in precision cancer therapy, offering new possibilities for safer and more effective treatments. However, further research is required to address long-term biocompatibility, control mechanisms within the human body, and clinical validation. This study highlights the transformative potential of integrating microscopic robots into future cancer treatment strategies, contributing to the advancement of personalized medicine.